A rare presentation of a pyosalpinx in a post-menopausal woman - Rao, Ashwin; Rani, Reddi; Rathod, Setu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Primary fallopian tube carcinoma is a rare tumour of the female genital tract with an incidence of 0.1-1.8% of all genital malignancies, which is generally an intra-operative or a histological diagnosis. It is a tumour that resembles epithelial ovarian cancer. A 61-year-old postmenopausal woman presented with complaints of continuous bleeding per vaginum with history of loss of appetite and weight for 6 months. She was also a known diabetic and hypertensive. On examination, per abdominal, per speculum and per vaginal findings were unremarkable. A transvaginal ultrasonography done previously showed fluid in the endometrial cavity suggestive of hematometra/pyometra due to cervical stenosis. A fractional curettage done previously had shown strips of acanthotic squamous epithelium in the endocervical curetting. She underwent abdominal hysterectomy with bilateral salpingo ovariectomy. Histopathological findings were suggestive of primary fallopian tube adenocarcinoma. Hence the patient was advised chemotherapy followed by a second look laparotomy. Preoperative diagnosis of fallopian tube carcinoma is difficult due to the silent course of this neoplasm and is usually first appreciated at the time of operation or by a pathologist. The treatment approach is similar to that of ovarian carcinoma, and it should consist of a total abdominal hysterectomy with bilateral salpingo-ovariectomy, omentectomy and lymph node dissection from the pelvic and the para-aortic regions.